2021
DOI: 10.1021/acs.langmuir.1c00731
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Lipid Nanotubules by Ultrasonic Drag Force

Abstract: This work reports a new method of fabricating lipid nanotubules using ultrasonic Stokes drag force in theory and experiment. Ultrasonic Stokes drag force generated using a planar piezoelectric ultrasonic transducer in a remotely controllable way is introduced. When ultrasonic Stokes drag force is applied on lipid vesicles, the lipid nanotubules attached can be dragged out from the lipid film. In order to demonstrate the formation mechanism of the lipid nanotubules produced by ultrasonic drag force clearly, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In terms of the origin and driving force for the formation of the tubule-like structure, it is reported that two major protocols are there for the formation of such an extended tubule-like structure. One of the extensively accepted protocols is the deformation of the vesicular morphology of the lipids induced by foreign biomolecules, like nanoparticles, external dragging force, proteins, etc. Another protocol for the formation of a long tail-like tubular structure is reported to take place via the process of the self-assembly of the lipid molecules. In our present study, the maximum loss of the bilayer rigidity and hence the disruption are found to take place in the case of the interaction of the 1:1 cross fibrils made up of 10 mM Met and 10 mM Phe. Hence, it is expected that the interaction of the 1:1 cross fibrils of Met and Phe with the lipid vesicle membrane leads to the extraction of the lipids from the vesicles through the bilayer disruption followed by the tail formation by those extracted lipid molecules, apparently looking like a tube.…”
Section: Resultsmentioning
confidence: 49%
“…In terms of the origin and driving force for the formation of the tubule-like structure, it is reported that two major protocols are there for the formation of such an extended tubule-like structure. One of the extensively accepted protocols is the deformation of the vesicular morphology of the lipids induced by foreign biomolecules, like nanoparticles, external dragging force, proteins, etc. Another protocol for the formation of a long tail-like tubular structure is reported to take place via the process of the self-assembly of the lipid molecules. In our present study, the maximum loss of the bilayer rigidity and hence the disruption are found to take place in the case of the interaction of the 1:1 cross fibrils made up of 10 mM Met and 10 mM Phe. Hence, it is expected that the interaction of the 1:1 cross fibrils of Met and Phe with the lipid vesicle membrane leads to the extraction of the lipids from the vesicles through the bilayer disruption followed by the tail formation by those extracted lipid molecules, apparently looking like a tube.…”
Section: Resultsmentioning
confidence: 49%
“…Although researchers have achieved how to manipulate the microparticle medium with SAW, keeping the accuracy control of SAW still is a technical challenge. In recent years, SAW microfluidic technology has developed quickly to control the acoustic radiation force, acoustic streaming, atomization, suspension, and micro-jetting, which can meet partial requirements in the field of DNA nanoparticles encapsulation [74] , acoustic tweezers for particle and fluid micromanipulation [75] , preparation of nanoscale contrast agents and lipid nanotubes [76] , [77] . Furthermore, sonodynamic therapy, as a new non-invasive treatment method, is widely used to process ultrasonic thrombolysis or deliver drug particles into the cell by releasing nanobubble pressure, which is activated through the effect of cavitation, fluid flow, and acoustic radiation force [78] , [79] , [80] .…”
Section: Demand Design Based On Acting Mediummentioning
confidence: 99%